PENGUJIAN DISIPLIN PASAR PERBANKAN BERDASAR POSISI CAR, LDR, ROA DAN NPL - Riandika, ASditya Febri; ., Taswan (Proceeding SENDI_U, 2015)
This study aims to examine the influence of the banks internal analysis of the deposit growth by signaling theoryperspective and market discipline. Corresponding signal theory that positive internal conditions increase theconfidence that the company has a high quality to attract the interest of the depositors. In this study, researchersused purposive sampling and sample size 349 companies obtain conventional bank in Indonesia, Bank Indonesiaregistered in the year 2008 to 2012 includes the factors of the Capital Adequacy Ratio (CAR), Loan Deposit Ratio(LDR), Return on Assets (ROA ), and Non-Performing Loans (NPL). Hypothesis testing using t - test with asignificance level of 5%. Based on the results of that study showed a significant positive effect of CAR, LDRsignificant negative effect, significant positive influence ROA and NPL significant negative effect.KeywordS : Deposit Growth, Capital Adequancy Ratio, Loan Deposit Ratio, Return on Assets, Non Performing